(untitled) (Research, Society and Development, 2021)
Postpartum hemorrhage (PPH) is defined as a blood loss ≥ 500 mL that occurs within 24 hours after delivery, when this loss is greater than 1,000 mL it is considered severe. PPH is among the leading causes of severe maternal morbidities, accounting for about 25% of all deaths of pregnant women worldwide, especially in low-income countries. In Brazil, it is the second leading cause of maternal death. This study aimed to analyze the scientific production on interventions used to prevent and control postpartum hemorrhage. This was a bibliographic research of the integrative literature review type; studies were extracted from the PubMed (National Library of Medicine), BVS (Virtual Health Library) and CINAHL (Cumulative Index to Nursing and Allied Health Literature) databases. We used 14 studies published from 2016 to 2021. The predominant level of evidence was II - randomized clinical trial, 11 studies obtained grade recommendation A. The results conclude that the interventions analyzed as effective for the prevention of postpartum hemorrhage were: oxytocin, misoprostol, carbetocin, ergometrine or methylergometrine, active management in the third period of labor and uterine artery ligation. In the control of PPH were: tranexamic acid, uterine balloon tamponade (BTU) and the non pneumatic anti-shock suit (NASG).